2013
DOI: 10.1080/10410236.2012.702644
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual Health Communication: Distinctive Needs of Providers from Five Specialties

Abstract: Understanding providers’ expectations and needs for medical interpreters can provide important insight into the dynamics and process of interpreter-mediated medical encounters. This is one of the first mixed-methods studies on the similarities and differences of providers’ views of interpreters across five specialties (i.e., obstetrics/gynecology, emergency medicine, oncology, mental health, and nursing). The two-stage studies include interview data with 39 providers and survey data with 293 providers. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 42 publications
0
13
0
3
Order By: Relevance
“…Thus, the physician's awareness of when and how to use an interpreter is important (Hsieh et al . ). When there is no interpreter and a provider is forced to act as the interpreter in a consultation, this can have a negative impact on communication outcomes because the ability to balance the two roles at the same time has been shown to be challenging (MacFarlane et al .…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the physician's awareness of when and how to use an interpreter is important (Hsieh et al . ). When there is no interpreter and a provider is forced to act as the interpreter in a consultation, this can have a negative impact on communication outcomes because the ability to balance the two roles at the same time has been shown to be challenging (MacFarlane et al .…”
Section: Discussionmentioning
confidence: 97%
“…For example, when an interpreter believes that expressing empathy toward patients can facilitates QEC, we predict that they are likely to do so. However, because providers from different specialties may hold different expectations about the needed interpreter behaviors to achieve QEC, they may hold divergent evaluations about such practices [60,72].…”
Section: Discussionmentioning
confidence: 98%
“…Interpreters actively provide emotional support and minimize negative attitudes/emotions during medical encounters by noting the needs to bridge cultural differences, enhance provider-patient bonding, and ensure quality care [28,40,60,71]. A recent study found that nurses highly value interpreters' function as patient ally [72], which echoes with the general tasks of nurses in which they often help patients to voice their concerns, address their information needs, and provide emotional support [26,73].…”
Section: Empathy As Emotion Work In Healthcare Interpretingmentioning
confidence: 95%
“…It might also be useful to address the roles of any bicultural support workers or family members present. Doctors, patients, bicultural support workers and/or family members may not understand that accurate interpreting does not require speech to be translated word for word (a misconception which has also been identified in other literature; Hadziabdic, Lundin, & Hjelm, ), and that a role as patient ally, advocate or support (including talking about health issues outside the consultation) may be viewed by trained interpreters as contravening professional ethics of impartiality, and undermining the doctor–patient relationship (Butow et al., ; Hsieh, Pitaloka, & Johnson, ). Doctors and patients may not be aware of ethical dilemmas for interpreters or of their emotional responses.…”
Section: Discussionmentioning
confidence: 99%